War and peace in international rivalry - Diehl, Paul F. (Paul Francis) (University Of Michigan Press, 2001)
"War and Peace in International Rivalry provides the first detailed analysis of international rivalries, the long-standing and often violent confrontations between the same pairs of states. The book addresses conceptual components of rivalries and explores the origins, dynamics, and termination of the most dangerous form of rivalry - enduring rivalries - since 1816"--Jacket.